Absence of food aversion learning in the polyphagous noctuid, spodoptera litura (F.) following intoxication by deleterious chemicals - Ghumare, S. S.; Mukherjee, Samindra N. (Journal of Insect Behavior, 2005)
The objective of this study was to determine whether the presence of a deleterious chemical in a preferred host plant could alter the feeding preference of a polyphagous insect. The preference of the Asian armyworm, Spodoptera litura (F.) (Lepidoptera: Noctuidae) for castor, Ricinus communis (L.) (family: Euphorbiaceae) relative to cabbage, Brassica oleracea (L.) (family: Brassicaceae) was quantified by two separate two-way choice tests (without treatment and with treatment of the test chemicals used in the present study) with naive third instar larvae each time. This was followed, by continuous feeding (48 h) on the preferred host treated with the test chemicals and using naive third instar larvae for conditioning. Each treatment consisted of one of nine compounds, including seven naturally occurring allelochemicals (viz. (-)-alpha-pinene, (-)-beta-pinene, beta-myrcene, D-limonene, cineole, rutin, and ajwain oil) and two synthetic insecticides (viz. alphamethrin and malathion). Following this, a two-way choice test was repeated with the same batch of larvae without any test chemical. Larvae continued to maintain preference for castor despite exposure to the deleterious chemicals. Among the test chemicals, D-limonene and alphamethrin caused significant reduction in growth. Preference for castor was not overcome by exposure to novel deleterious chemicals, suggesting that aversion, though experienced is not learned.
Keywords: aversion learning; deleterious chemicals; polyphagy; preference; Spodoptera litura

Flufenoxuron, an acylurea insect growth regulator, alters development of Tribolium castaneum (Herbst) (Coleoptera :tenebrionidae) by modulating levels of chitin, soluble protein content, and HSP70 and p34(cdc2) in the larval tissues - Salokhe, S.; Sarkar, A.; Kulkarni, A.; Mukherjee, Samindra N.; Pal, J. K. (Pesticide Biochemistry and Physiology, 2006)
The effect of sublethal concentrations, 0.00141% (LC20), 0.00251% (LC30), and 0.0036% (LC40) of a dispersible formulation of an acylurea insect growth regulator, flufenoxuron (Cascade) on certain biochemical parameters in the larvae of Tribolium castaneum was investigated. When neonates were fed on diet treated with sublethal concentrations for 24 It, it was observed that at all concentrations tested, there was a significant reduction in chitin content on the 15th day of development. Total soluble protein content at LC20 and LC30 decreased with increasing age of the larvae. At LC20 and LC40 concentrations there was a progressive increase in the protein: chitin ratio as a function of increase in age of the larvae. SDS-PAGE analysis of the larval tissue extracts indicated gross quantitative changes in some of the protein bands (MW 50-97 kDa). Western blot analysis revealed significant increase in the level of HSP70 in the extracts of larvae fed on LC30 treated diet, on the 7th and 10th day of development in the decreasing order. Conversely, a significant decrease in the hyper-phosphorylated form of p34(cdc2) kinase due to flufenoxuron treatment indicating modulation of cell cycle regulation was observed. Thus, sublethal concentrations of flufenoxuron alter expression of developmentally regulated proteins, HSP70 and p34(cdc2) and chitin formation in a stage-specific manner thereby resulting developmental abnormalities in T castaneum. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: chitin; Development; flufenoxuron; HSP70; p34(cdc2); phosphotyrosine; sublethal effects; total soluble proteins; Tribolium castaneum

Development and application of a method for analysis of lufenuron in wheat flour by gas chromatography-mass spectrometry and confirmation of bio-efficacy against Tribolium castaneum (Herbst) (Coleoptera : Tenebrionidae) - Ahire, Kedar C.; Arora, Manjit S.; Mukherjee, Samindra N. (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2008)
A new analytical method using gas chromatography with mass spectrometry (GC-MS) for the quantitative determination of lufenuron, a benzoylphenylurea (BPU) class of insecticide, from wheat flour has been developed and applied for time-dependant residue monitoring in treated wheat flour. The analyte was extracted from wheat flour by a single step solid-liquid extraction by using ethyl acetate and subsequently cleaned up using the Primary Secondary Amine as a sorbent prior to GC-MS analysis. The present method provides sufficient sensitivity as reflected by the values of limit of detection (LOD) and limit of quantification (LOQ), 5 ng/mL (S/N similar to 3) and 50 ng/mL (the lowest validation point on the calibration curve), respectively. The calibration curve showed an excellent linearity in the concentration range of 50-1000 ng/mL (r(2) = 0.998). The average recovery for spiked samples at three concentrations (150, 300, and 450 ng/g) was 98.23 +/- 2.52% R.S.D. The method was applied for the determination of lufenuron residues in treated wheat flour samples. Simultaneous determination of bio-efficacy of lufenuron residues was also carried out against the red flour beetle, Tribolium castaneum to correlate the actual residual effect of lufenuron as detected by the analytical method, over a period of 3 months. The findings revealed that the residual concentration of lufenuron were neither uniform nor in descending order over a period of 3 months in wheat flour, possibly because of an uneven dispersal in the treated wheat which was subsequently milled into flour, as confirmed by GC-MS analysis. However, the residues of lufenuron were sufficient to produce 100% mortality of T. castaneum larvae up to 3 months. The results have been discussed in view of the potential of lufenuron as a candidate molecule for the control of stored product pests. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: bio-efficacy; GC-MS; lufenuron; method development; residue analysis; Tribolium castaneum; Wheat

Effect of sub-lethal concentrations of insect growth regulator, lufenuron on larval growth and development of Aedes aegypti - Salokhe, S. G.; Mukherjee, Samindra N.; Deshpande, S. G.; Ghule, V. P.; Mathad, J. R. (Current Science, 2010)
The effect of sub-lethal concentrations (LC20 = 0.0002 and 0.001 ppm, and LC40 = 0.002 and 0.02 ppm for II and IV instar larvae respectively) of a dispersible concentrate formulation of the insect growth regulator, lufenuron on larval growth and development of Aedes aegypti was studied. When II and IV instar larvae were subjected to the above-mentioned sub-lethal concentrations of lufenuron through the culture medium, there was a significant increase in the time taken for pupation (17.2 +/- 0.74 and 11.4 +/- 0.8 days for II and IV instar LC20-treated larvae respectively, and 19 +/- 0.89 and 14.6 +/- 1.0 days for II and IV instar LC40-treated larvae respectively). Also, there was increase in the time taken for adult emergence 3.8 +/- 0.83 and 5.4 +/- 0.83 days from pupation of LC40-treated II and IV instar larvae respectively). There was 28.1 +/- 2.06% and 43.59 +/- 0.87% reduction in pupation in LC20 of lufenuron-treated II and IV instar A. aegypti larvae respectively. Also, with LC20 of lufenuron-treated II and IV instar larvae there was 43.54 +/- 5.12% and 43.59 +/- 0.87% reduction in adult emergence respectively. Further, it was observed that II instar larvae treated with LC20 of lufenuron developed into 25.8 +/- 2.08% deformed adults. In LC40-treated II instar larvae there was 33.72 +/- 2.38% reduction in pupation and 63.44 +/- 4.76% reduction in adult emergence. Also, it was observed that there was 54.84 +/- 3.9% and 61.3 +/- 5.2% reduction in pupation and adult emergence respectively, in IV instar larvae treated with LC40 of lufenuron. The reduction in pupation of the IV instar larvae treated with LC40 of lufenuron was due to failure of the larvae to undergo pupation. These studies are fundamental to the use of lufenuron in A. aegypti management.
Keywords: Aedes aegypti; larval growth and development; lufenuron; sub-lethal concentration

Evaluation of the insect growth regulator lufenuron (MatchA (R)) for control of aedes aegypti by simulated field trials - Salokhe, S. G.; Deshpande, S. G.; Mukherjee, Samindra N. (Parasitology Research, 2012)
The insect growth regulator, Lufenuron, at concentrations of even multiples of LC90 (determined under laboratory conditions) was tested against the III instar larvae of Aedes aegypti under simulated field conditions. For all concentrations tested, 100 % mortality of the larvae was observed within 24 h of exposure to Lufenuron-treated water. In experiments with LC90 x 4 Lufenuron concentration and where 15 % of water volume was replaced daily, percent mortality of the larvae was reduced to 40 % after the 54th day of treatment. Percentage mortality of the III instar larvae on the 54th day was higher in water with LC90 x 6 concentration than that observed for water with LC90 x 4 of Lufenuron. In the experiments with LC90 x 4 and LC90 x 6 concentrations of Lufenuron where 15 % of water volume was replaced weekly, larval mortality obtained after the eighth week was 68.75 and 88.33 %, respectively. In LC90 x 4 and LC90 x 6 of Lufenuron-treated stagnant water (without replacement of water), the percent mortality of the larvae on the 55th day was 65 and 90 %, respectively. Introducing a fresh batch of III instar A. aegypti larvae in the Lufenuron-treated waters revealed that residual activity of Lufenuron was sustained for 45 days after the treatment. All these experiments revealed that Lufenuron not only affects the prevalence of the A. aegypti larvae but also induces the development of abnormal adults.